Antibacterial Activity Test of Endophytic Fungi Extraction Kasumba Turate (Carthamus tinctorius L.) Leaves From Galesong against Digestive Tract Infection - Amin, Muhammad; Kosman, Rachmat; Rusli, Rusli (Journal Microbiology Science, 2024)
Digestive tract infection is still a significant health problem in Indonesia, it caused by pathogenic bacteria. Kasumba turate (Carthamus tinctorius L.) is a medicinal plant that empirically used as measles drug with several compounds such as flavonoids, quinocalcones, polyacetylenes, alkaloids, fatty acids, steroids, proteins and polysaccharides and kasumba turate (Carthamus tinctorius L.) leaves are believed to have antimicrobial activity against several microbes pathogens such as E.coli and S.aureus. This research was conducted to determine endophytic fungi isolates from kasumba turate (Carthamus tinctorius L.) leaves that can provide activity against bacteria that cause digestive tract infections seen from the bioautography profile determination. Three endophytic fungi isolated from kasumba turate (Carthamus tinctorius L.) leaves were purified and observe macroscopically. After purification an antibacterial screening test was conducted by observing the inhibition zone of each isolate; the isolate with largest inhibition zone is IFEDKT-03. Isolates were fermented for 21 days, mycelia and supernatant were separated, and extraction was performed. The endophytic fungi extract of kasumba turate (Chartamus tinctorius L.) leaves has antibacterial activity against Escherichia coli, Salmonella typhi, Shigella dysenteriae, and Vibrio cholera as indicated by Rf values of 0.23, 0.41, 0.49, 0.56, 0.70 and 0.76